Effect of surface conditioning techniques on the resistance of resin composite core materials on titanium posts - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2003)
Objective: This study evaluated the resistance of various post and core materials against torsional forces on differently conditioned titanium posts. Method and materials: One hundred fifty pure titanium posts (DIN 17850-Ti4/3.7065) were conditioned utilizing Silicoater Classical, Silicoater MD, Rocatec, Kevloc, and Siloc. Subsequently, three post and core materials (Adaptic, Coradent, Ti-Core) were applied to titanium posts that were previously coated with a light-cured opaquer (Dentacolor). Thirty sandblasted titanium posts were used as reference for each core material. Following thermocycling (5degreesC to 55degreesC, for 30 seconds or 5,000 cycles), maximum torsional forces were determined with an electronic torque movement key. Results: Kruskal-Wallis, Mann-Whitney U-tests indicated significant differences between Adaptic, Coradent, Ti-Core (20.9 dNm, 18.84 dNm, and 18.62 dNm, respectively). There were no significant differences between Silicoater Classical (18.56 dNm), Silicoater MD (18.18 dNm), and Rocatec (16.95 dNm), while Siloc exhibited the highest results (20.44 dNm). Kevloc demonstrated significantly lower results (10.43 dNm) than those of other systems and the control group (14.49 dNm). Conclusion: Resistance of core materials against torsional forces on titanium posts increased with the use of chemical surface conditioning techniques, while the system using only acrylization did not improve the resistance in comparison to the unconditioned posts.
Keywords: post and core materials; surface conditioning techniques; titanium posts; TORSIONAL FORCES; RETENTION; BOND; STRENGTH; CEMENTS